Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 51 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Eleutherodactylus dilatus (Davis & Dixon, 1955)", "Country is Mexico", { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Literature Occurrence" ] } ] } The dataset includes 51 records from 6 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001353-160526112335914/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences